Ivory pearl - Manchette, Jean-Patrick, 1942-1995 (New York Review Books classics., 2018)
"Set in Cuba's Sierra Maestra in the 1950s, in the days leading up to the Revolution--Manchette's unfinished masterpiece with a fearless female protagonist. Four of the ten titles in Jean-Patrick Manchette's celebrated 1970s cycle of hard-boiled novels, which the author originally dubbed neo-polars, or "neo-crime novels," have now appeared in English translation. Manchette is beginning to have a significant following among English-language readers, as witness chatter in cyberspace, favorable reviews, increasing sales, and the fact that the latest entrant, The Mad and the Bad (New York Review Books), won the 2014 French-American Foundation Translation Prize for Donald Nicholson-Smith. Ivory Pearl, aka Princesse du sang, published posthumously -and unfinished- in 1996, is considered by many French critics to be Manchette's masterpiece. In the early 1980s Manchette abandoned his attempt to "press the roman noir into the service of the social revolution" and turned his pen to other things. By the end of that decade, however, he resolved to start anew, though now working on a broader, "geopolitical" canvas. Inspiration came now less from Hammett's Red Harvest than from John Le Carre and, especially, from the works of Ross Thomas that Manchette had been translating. Sadly, Manchette's early death from cancer in 1995 put an end to this grand project. What remains, however, is Ivory Pearl, set mainly in Cuba's Sierra Maestra in the 1950s. The book will not disappoint those who admire Manchette's mastery of suspense and penchant for dauntless feminine protagonists"--